Keamanan Non-Tradisional dan Regulasi Pekerja Seks: Studi Perbandingan Kebijakan Indonesia dan Thailand dalam Perspektif Human Security - Valen Intanulsitta; Agussalim Burhanuddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study compares sex work regulations in Indonesia and Thailand through the lens of human security. Using qualitative comparative literature approach, the research analyzes four core dimensions including health, economy, legal protection, and social inclusion. Findings show that Indonesia still relies on criminalization, which exacerbates vulnerability, restricts access to health services, and reinforces stigma. Conversely, Thailand is undergoing a regulatory transition marked by community engagement, harm reduction practices, and early steps toward decriminalization. However, Thailand’s policy remains incomplete in addressing the rights of migrant and transgender sex workers. The study concludes that while Thailand provides a more inclusive model, both countries require further policy reform distinguishing voluntary sex work from exploitation, strengthening grassroots organizations, and regional policy harmonization under ASEAN human rights framework.